2009
DOI: 10.1111/j.1365-2095.2009.00668.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary carbohydrate-to-lipid ratios on growth performance, body composition, nutrient utilization and hepatic enzymes activities of herbivorous grass carp (Ctenopharyngodon idella)

Abstract: Six isonitrogenous (390 g kg )1 ) and isoenergetic (16.2 kJ g )1 ) diets with varying carbohydrate : lipid (CHO : L) ratios (202.5-1.74), were fed to triplicate groups of 25 fish in indoor recirculation system. Over 8-week-growth trial, best weight gain (WG), specific growth rate, feed conversion ratio, protein efficiency ratio and protein production value (P < 0.05) were observed in fish-fed diets with CHO : L ratio of 7.5. Fish fed either the lowest (1.7) or highest (202.5) CHO : L ratio tended to produce lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
64
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(93 citation statements)
references
References 48 publications
27
64
2
Order By: Relevance
“…These references reported that high carbohydrate had no significant effect on growth performances. In contrast, other research reported that excessive carbohydrate levels had effect on growth performances by reducing the growth rate, and increasing FCR in blunt snout bream [23] and grass carp (Ctenopharyngodon idellus) [24]. The reason of difference from our result may be related to the different carbohydrate content in different diets.…”
Section: Discussioncontrasting
confidence: 99%
“…These references reported that high carbohydrate had no significant effect on growth performances. In contrast, other research reported that excessive carbohydrate levels had effect on growth performances by reducing the growth rate, and increasing FCR in blunt snout bream [23] and grass carp (Ctenopharyngodon idellus) [24]. The reason of difference from our result may be related to the different carbohydrate content in different diets.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar findings were obtained in top mouth culter (Erythroculter ilishaeformis Bleeker) (Liu et al, 2008) and European whitefish (Coregonus lavaretus) (Vielma et al, 2003). However, some other studies reported no significant differences in gilthead sea bream (Sparus aurata) (Enes et al, 2008), largemouth bass (Micropterus salmoides) (Amoah et al, 2008) and grass carp (Ctenopharyngodon idellus) (Gao et al, 2010).…”
Section: Resultssupporting
confidence: 64%
“…More surprisingly, the induction of GK activity by carbohydrates is lower in omnivorous fish known to utilise carbohydrates well, i.e. common carp (164,211) , Indian carp (Catla catla) (212) , silver sea bream (Pagrus auratus) (213) , zebrafish (Danio rerio) (214) , tilapia (Oreochromis niloticus x O. aureus) (215) and grass carp (Ctenopharyngodon idella) (216) . This suggests that induction of hepatic GK is not a limited factor to use dietary carbohydrates.…”
Section: Nutritional Regulation Of Hepatic Glucokinasementioning
confidence: 99%